2014
DOI: 10.1039/c4dt00658e
|View full text |Cite
|
Sign up to set email alerts
|

Direct hydrosilylation by a zirconacycle with β-hydrogen

Abstract: Azasilazirconacycle Cp2Zr{κ(2)-N(SiHMe2)SiHMeCH2} (1) and formaldehyde react through an uncatalyzed addition reaction (hydrosilylation) to form an exocyclic methoxysilyl-substituted zirconacycle. Although 1 contains 2-center-2-electron SiH groups, this transformation parallels the reactions of non-classical [Cp2ZrN(SiHMe2)2](+) ([2](+)) with carbonyls. Reactions of 1 with a series of nucleophilic and electrophilic agents were explored, as well as reactions of related β-SiH-containing silazidozirconium compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Thus, the basicity of the bulkier silazido ligand N­(SiMe 3 ) t Bu was invoked for reactions of Ln­{N­(SiMe 3 ) t Bu} 3 (Ln = Y, La) as a precursor to homogeneous hydroamination catalysts . Still, the SiH group in N­(SiHMe 2 ) 2 provides a valuable spectroscopic handle for both NMR and IR analysis, stabilization of coordinatively and electronically unsaturated metal centers through labile secondary interactions, ,,, and a site for reactivity. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the basicity of the bulkier silazido ligand N­(SiMe 3 ) t Bu was invoked for reactions of Ln­{N­(SiMe 3 ) t Bu} 3 (Ln = Y, La) as a precursor to homogeneous hydroamination catalysts . Still, the SiH group in N­(SiHMe 2 ) 2 provides a valuable spectroscopic handle for both NMR and IR analysis, stabilization of coordinatively and electronically unsaturated metal centers through labile secondary interactions, ,,, and a site for reactivity. …”
Section: Introductionmentioning
confidence: 99%
“…The Zr–P distance of 2.71 Å is unexceptional and lies in the typical range observed for Cp 2 Zr–PMe 3 fragments. 47–49 The observation of a longer Zr–W distance in 3a compared to 1 (δ d Zr–W = 0.3 Å) suggests that metal–metal interactions play a negligible role in its bonding (see DFT section). Consistently, electron density corresponding to a bridging hydride was located in the Zr coordination plane, at an approximate distance of 2.0 Å from Zr and 1.7 Å from W, establishing a Zr–H–W angle of about 130° (average between the two independent molecules in the cell).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, Ln↼E–Si interactions typically are structural features of electron-poor complexes. , Recently, a few examples reveal that d 0 M↼H–Si or Ln↼H–Si interactions are reactive. The cationic or zwitterionic zirconium disilazidos [Cp 2 ZrN­(SiHMe 2 ) 2 ] + and Cp 2 Zr­{N­(SiHMe 2 )­(SiHMeCH 2 B­(C 6 F 5 ) 3 )} react with acetone and formaldehyde to give hydrosilylation products [Cp 2 ZrN­(SiMe 2 OR) 2 ] + (R = Me, CHMe 2 ) or Cp 2 Zr­{N­(SiMe 2 OR)­(Si­(OR)­MeCH 2 B­(C 6 F 5 ) 3 )}. , In addition, [Cp 2 ZrN­(SiHMe 2 ) 2 ] + and 4-dimethylaminopyridine (dmap) react to give a zirconium hydride containing a dmap-coordinated silazido, [Cp 2 ZrH­{N­(SiHMe 2 )­(SiMe 2 dmap)}] + , suggesting that the silicon is the most accessible electrophilic site in [Cp 2 ZrN­(SiHMe 2 ) 2 ] + . In the initial communication of the present work, we reported that Y­{N­(SiHMe 2 )­dipp} 3 (dipp = 2,6-diisopropylphenyl) and acetophenone react via hydrosilylation .…”
Section: Introductionmentioning
confidence: 99%